Wheel Rail Wear Prediction and Dynamic Performance Analysis of Linear Metro - Chen, Long; Feng, Ding; Yu, Yanxia; Zeng, Yunfeng (European Journal of Computational Mechanics, 2022)
In order to improve the safety of linear motor metro operation, the wheel rail wear prediction and dynamic performance analysis of linear motor metro are carried out. Firstly, the working principle and evolution process of the linear motor are analyzed, and the traveling wave magnetic field and slip ratio of the linear motor are calculated. Secondly, the friction principle between wheel and rail is analyzed, and the running data of wheel and rail area are collected by MiniProf series profiler. By calculating the wear energy flow density and wear mass flow density of wheel rail contact surface, the relationship between wear coefficient and energy flow density is obtained, and the wheel rail wear area is obtained, so as to complete the prediction of wheel rail wear. Finally, the running resistance of Metro is analyzed, including mechanical resistance and aerodynamic resistance. Combined with the calculation results of Metro kinetic energy and electromagnetic, the position of linear motor is obtained by modal superposition method in the elastic coordinate system, and the dynamic equation of linear motor Metro is constructed to complete the dynamic performance analysis of Metro. The experimental results show that this research method can accurately predict the wear of linear motor metro, and can study the running stability of Metro from the two aspects of horizontal stability and derailment coefficient.